Pengaruh Latihan Yoga Terhadap Aktivitas Fungsional Pada Kasus Osteoartritis Genu (Literature Review) - Sahlah Yusuf Baisa; Noraeni Arsyad; Zulfikar H Wada (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to examine the effect of Yoga Exercise on functional activities in conditions of Osteoarthritis Genu based on collected literature. This research method uses a literature review approach. Literature was obtained from 3 databases: Google Scholar, ScienceDirect, and Pubmed. The research samples were Osteoarthritis Genu patients; over 18 years old; yoga exercise; male or female gender; year of publication on the last 10 years (2013- 2023); The variable measured is functional activity (WOMAC, KOOS, Gait Speed Test, SF-36, Sit to Stand Test). Exclusion criteria were non-knee osteoarthritis patients; do exercise other than yoga exercise. Based on 13 literatures that have been collected, it was found that the number of published literature in the last 10 years was 2 studies and in the last 5 years there were 11 studies with literature study designs, RCT and Quasi- Experimental. The number of participants was 614 participants, with male and female genders with an average age of 50-65 and above. The OAG criteria obtained on average were chronic OAG (>3-6 months); the results showed that yoga practice had a significant effect on functional activity with a p-value of p<0.05; the form of yoga exercise used predominantly was yoga exercise with the type of mat yoga with movements in the form of warm-up, breathing exercise, yoga posture, and meditation; with an average dose of 4-8 weeks, 2-5 times per week, with a duration of exercise for 30-60 minutes. After evaluating the results of the most significant influence on functional activity with average p-value of p<0.001. Overall, this study saw that there was a significant effect of yoga exercise on functional activities in Osteoarthritis Genu patients and there was an alternative form of modification of yoga practice in elderly patients, using chair yoga, with the conclusion that yoga practice must use high doses and intensity.